2021
DOI: 10.7759/cureus.17634
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Chronic Diseases in Individuals Responding to a Measure for the Initial Screening of Depression and Reported Feelings of Being Down, Depressed, or Hopeless

Abstract: IntroductionFeeling down, depressed, or hopeless may provide a comprehensive measure for physicians to utilize, allowing a possible way to assess risk for chronic diseases. MethodsA face-to-face, in-home, validated survey was conducted on participants aged 16 and older. Trained interviewers administered the questionnaire through the Computer-Assisted Personal Interview (CAPI) system. Through this measure, responses such as feelings of depression, diagnosis of high cholesterol, high blood pressure, diabetes, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Several studies have shown a positive correlation between BMI and depression-like symptoms [ 19 , 20 ]. In contrast to our initial hypothesis, when combining the prevalence percentage of being overweight or obese among men and women according to each depression symptom from the questionnaire, men who had a higher prevalence of being overweight or obese chose “more than half the days” or “nearly every day” for each depression category, except for the percentage of men who responded “more than half the days” when asked about being better off dead.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a positive correlation between BMI and depression-like symptoms [ 19 , 20 ]. In contrast to our initial hypothesis, when combining the prevalence percentage of being overweight or obese among men and women according to each depression symptom from the questionnaire, men who had a higher prevalence of being overweight or obese chose “more than half the days” or “nearly every day” for each depression category, except for the percentage of men who responded “more than half the days” when asked about being better off dead.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) can be calculated via mathematical operations where height and weight values are used to estimate the health status of a person [5]. BMI as a measurement is typically used to gauge the risk of developing chronic conditions such as diabetes, hypertension, depression, and cancer [4][5][6][7][8]. The BMI calculation will fall within a numerical range, which places an individual into one of four categories.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that no agreement has been reached on the association of obesity and lipid-associated indices with T2DM. For instance, the BMI is frequently used to estimate the likelihood of contracting chronic diseases including diabetes, hypertension, depression, and cancer (14)(15)(16)(17). However, compared to other measurements like WC, WHR, and WHtR, BMI was the least accurate predictor for cardiovascular risk factors such as diabetes, hypertension, and dyslipidemia in the study conducted by Lee et al (18).…”
Section: Introductionmentioning
confidence: 99%